Electrochemical fluorination of metals for fluoride ion battery application - Tan, Nan Sheng (2014)
Fluoride ion battery consist of two electrodes, an anode and a cathode, electrolyte to transfer the charges , separator to prevent the cathode and anode from touching and a casing to hold all the components in place. All the components are important for the fluoride ion battery to function. In this report, the focus was on the finding the ideal material for some of components listed which include the electrodes and the casing. While finding the ideal material, the predetermined electrolyte tetramethylammonium fluoride in propylene carbonate( TMAF in PC) that was previously identified would be tested for its functionality.